Fruit of the Devil - Erotic Short Story - Jones, S. Jones (Saga Egmont, 2024)
Good guy Romain exits life only to snag an otherworldly gig as the next \\\'In-Between\\\' - Earth\\\'s crucial balancer of Good and Evil. Selected by both God and Satan due to his overly virtuous life devoid of thrills, he now faces the ultimate challenge: seven days of intense training with Kiara - the seasoned veteran who can spice up his existence and introduce him to sinful temptation... Carrie S. Jones is a modern American writer who likes to play with different reading genres. From reality to fantasy, crime to romance, she likes to introduce eroticism into every universe.She wants everyone to be able to identify their fantasies, desires and even questions through stories that combine sensuality and ardour. Explore your true nature with this no-holds-barred short story writer.